Analisis Faktor-Faktor yang Mempengaruhi Minat Menabung di Bank Syariah pada Masyarakat Kabupaten Banyumas - Sodik Dwi Purnomo; Heru Cahyo; Siti Ainul Mukharomah (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to analyze the effect of financial literacy, trust, location, income, and perception of profit sharing on interest in saving in Islamic banks. This type of research is quantitative. The sampling technique was simple random sampling and a sample of 100 respondents. The method of analysis used multiple linear regression. The results showed that financial literacy and location did not affect the interest in saving in Islamic banks in the people of Banyumas Regency. trust, income and perception of profit sharing have a positive and significant effect on the interest in saving in Islamic banks in the people of Banyumas Regency. the need to improve the provision of information about Islamic banks such as Islamic principles and products in Islamic banks, so that public interest in saving in Islamic banks will increase.